PARTICIPATORY SELECTION OF PLANT SPECIES TO ENHANCE THE SUCCESS OF FOREST REHABILITATION IN BULUSARAUNG FOREST MANAGEMENT UNIT - Hayati, Nur; Prasetyawati, C. Andriyani; Dewi, Indah Novita; Yuliantoro, Isdomo; Tata, Hesti Lestari; Suharti, Sri; Dharmawan, I Wayan Susi; Rachmat, Henti Hendalastuti; Windyoningrum, Ayun; Khotimah, Husnul (Indonesian Journal of Forestry Research, 2025)
The success of forest area rehabilitation requires community involvement. The selection of plant species that are suitable to community preferences will substantially influence the success of rehabilitation efforts. Communities’ preferences for specific plant species may increase their willingness to care the plant. This research explored the importance of participatory plant species selection in supporting forest rehabilitation success of Cahaya Tala-Tala Forest Farmers Group (FFG) in the Bulusaraung Forest Management Unit (FMU), South Sulawesi, Indonesia by applying the agroforestry technique. The study employed the participatory rural appraisal approach in one village and involved 50 respondents. The results indicated that the FFG members’ preferences for specific plant species were categorized as being in the “affected” stage and positioned at the “preference” stage according to the hierarchy of effects model. The participation of the FFG members in forest rehabilitation activities at the Bulusaraung FMU is categorized as the “partnership” level. The selected multipurpose tree species are expected to substantially contribute to the community’s income and help the success of forest rehabilitation activities in Indonesia.